Associations amongst disease severity, religious coping and depression in a cohort of Jamaicans with sickle-cell disease - Morgan, Kai A.D. (Mental health, religion & culture, 2014)
The purpose of this study was to investigate the relationship between disease severity (sickle-cell type and hospital, emergency room and clinic emergency visits (CEU)), religious coping (positive and negative) and depression. This was accomplished through secondary analysis of a data set based on a Comprehensive Sickle Cell Standardized Questionnaire compiled by a multidisciplinary team of professionals from Duke University Medical Centre, and administered to persons with sickle-cell disease being treated at the Sickle Cell Unit on the University of the West Indies Campus between November 2008 and January 2009. Disease severity was not a good predictor of depression within the population. On the other hand, depression was found to correlate with positive and negative religious coping, such that increases in the former were associated with decreases in depression scores; while the reverse was noted for the latter (negative religious coping). The results shed light on issues that could possibly impact the treatment plan for such individuals.